Smart cat cage with Internet of Things - Teh, K. Y.; Yee, S.K.; Jong, S. L. (Penerbit UTHM, 2020)
Pets such as cats are always great companions. It is famous among human society. However, the efforts of taking care the cats when away from home are challenging. In this era, wireless network technology has taken over the world, and it revealed the possibility of remote controlling of any devices or systems. The fourth industrial revolution has begun with the introduction of Internet of Things (IoT) indicates the action of petting with IoT concepts is feasible. Since food, water, and temperature are the main concern for cats. A smart cat cage is developed with IoT petting system and live scene monitoring system. In IoT petting system, food feeding, water feeding and temperature control could be accessed with mobile phone application “Blynk” via an Internet connection. In the live scene monitoring system, the user can access the live streaming video captured by a camera module by using any web browser. Based on live streaming video, the user can monitor the cat behaviour and detect any emergency. The controlling and monitoring activities could be conducted as long as the WiFi connection is available. In future work, more features like cage cleaning, food and water dispenser storage level notification could be included.